Engineering mannosylated pickering emulsions for the targeted delivery of multicomponent vaccines. (January 2022) - Du, Yiqun; Song, Tiantian; Wu, Jie; Gao, Xiao-Dong; Ma, Guanghui; Liu, Yuchen; Xia, Yufei
Abstract: While research on cancer vaccines has made great strides in the field of immunotherapy, the targeted delivery of multiple effective components (rational-tailored antigens and adjuvants) remains a challenge. Here, we utilized the unique hierarchical structures of Pickering emulsions (particles, oil core, and water-oil interface) to develop mannosylated (M) Pickering emulsions (PE) that target antigen presenting cells and synergistically deliver antigenic peptides and the TLR9 agonist CpG (C) as an enhanced cancer vaccine (MPE-C). We chemically linked mannose residues to PLGA/PLAG-PEG nanoparticles and produced a dense array of mannose on the nanopatterned surface of Pickering emulsions, allowing for increased cellular targeting. Together with the inherent deformability of the oily core, MPE-C increased the droplet-cellular contact area and provoked the cellular recognition of mannose and CpG for enhanced immune activation. We found that MPE-C attracted a large number of APCs to the local site of administration, evidently increasing cellular uptake and activation. Additionally, we observed increased antigen-specific cellular immune responses, with potent anti-tumor effects against both E.G7-OVA and B16-MUCI tumors. Furthermore, MPE-C combined with PD-1 antibodies produced a significant tumor regression, resulting in synergistic increases in anti-tumor effects. Thus, through the strategic loading of mannose, antigens, and CpG, Pickering emulsions could serve as a targeted delivery platform for enhanced multicomponent cancer vaccines.